Preparation and characterization of silver/chitosan/gelatin bionanocomposites by chemical reducing method and their antibacterial activities - Lim, Jenn Jye (2013)
The aim of this study is to investigate the functions of polymers and size of nanoparticles on the antibacterial activity of silver bionanocomposites (Ag BNCs). In this research, silver nanoparticles (Ag NPs) were incorporated into biodegradable polymers, which are chitosan (Cts), gelatin and both polymers via chemical reduction method in solvent in order to produce Ag BNCs. Silver nitrate and sodium borohydride were employed as a metal precursor and reducing agent respectively. In addition, chitosan and gelatin were added as both polymeric matrix and stabilizer. The properties of Ag BNCs were studied based on function of the polymer weight ratio in relation to the use of chitosan and gelatin. These prepared Ag NPs were very stable over a long period (i.e. 4 months) in an aqueous solution without any sign of precipitants. The UV-vis spectra shown maximum absorbance bands for Ag BNCs were detected at 408, 416, 414, 413, and 414 nm, respectively. From the FTIR spectra, the vibrational band of Ag BNCs detected at ~1395 cm−1 could indicate the interaction between Ag NPs with chitosan and gelatin. The morphology of the Ag BNCs films and the distribution of the Ag NPs were characterized using Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). From the SEM image, Ag/Cts BNCs shown layered surfaces with small flakes, Ag/Cts/gelatin BNCs showed smooth layered surfaces and Ag/gelatin BNCs showed porous layered surfaces. In addition, the EDX spectra for Ag BNCs had confirmed the presence of elemental compounds in the Cts, gelatin and Ag NPs without any impurity peaks. From the TEM images, the results of average diameters of the Ag NPs in different weight composition of polymers were in the range of 2.90-11.25 nm. However, the TEM results also shown that aggregation of Ag NPs where there is an overlap of particles and larger particle size in chitosan only which contributed to the size of 11.25 nm compared with others samples which are 2.90 nm-4.38 nm. With the aid of XRD pattern, Ag BNCs films confirmed the face-centered cubic (FCC) type crystallographic planes of the Ag crystal. The XRD peaks at 2θ with value of around 38°, 44°, 64°, and 77° are well recognized to the 111, 200, 220, and 311 crystallographic planes of the FCC Ag crystals, respectively. The antibacterial activities of the Ag BNC films were examined against Gram-negative bacteria (E. coli and P. aeruginosa) and Gram-positive (S. aureus and M. luteus). The silver ions released from the Ag BNCs and their antibacterial activities were scrutinized. From TEM analysis and the result of antibacterial activity, Ag/Cts/gelatin BNCs exhibited better particle distribution as well as having high antibacterial activity. A simple way to prepare Ag/Cts/gelatin bionnanocomposites had been employed as previously there is no research on investigating the antibacterial activities of silver into both chitosan and gelatin.